No evidence of a causal relationship between ankylosing spondylitis and cardiovascular disease: a two-sample Mendelian randomization study - Zhong, Yan; Chen, YingWen; Zhang, XinYue; Cai, WenJun; Zhao, ChangWei; Zhao, WenHai (Frontiers in Cardiovascular Medicine, 2023)
Objective Observational studies have suggested an increased risk of cardiovascular disease in individuals with ankylosing spondylitis. However, these studies are prone to confounding factors and reverse causality. To address these limitations, we conducted a Mendelian randomization study to assess the causal relationship between AS and CVD. Methods The study population comprises 9,069 individuals with ankylosing spondylitis and 509,093 individuals with either of six common cardiovascular diseases and a related indicator. Causal analysis using summary effect estimates and inverse variance weighting were employed as the main methods. Results The CAUSE analysis showed no evidence of a causal relationship between AS and CVD. The odds ratios for total CVD, heart failure, myocardial infarction, valvular heart disease, ischemic heart disease, and venous thromboembolism, Arterial stiffness index, were as follows: OR, 1.01; 95% confidence interval, 0.96–1.05; P = 0.91; OR, 1.03; 95% CI, 0.99–1.08; P = 0.50; OR, 0.94; 95% CI, 0.86–1.03; P = 0.53; OR, 0.99; 95% CI, 0.94–1.04; P = 0.99; OR, 0.98; 95% CI, 0.91–1.04; P = 0.94; OR, 0.98; 95% CI, 0.91–1.04; P = 0.99; β, −0.0019; 95% CI, 0.97–1.01; P = 0.99. The IVW and weighted median methods also yielded consistent results, and no heterogeneity or pleiotropy was found. Likewise, a reverse Mendelian randomization analysis did not uncover a heritable causal relationship between AS and CVD. Conclusion This Mendelian randomization study does not support a causal relationship between AS and CVD. Further research is needed to confirm this association.